Kondisi Terumbu Karang di Pulau Kapoposang Kecamatan Liukang Tuppabiring Kabupaten Pangkajene Provinsi Sulawesi Selatan - Rombe, Katarina Hesty; Rosalina, Dwi; Rahmawati, Gita; Surachmat, Agus; Sabilah, Anisa Aulia; Rahman, Abdul; Hermawan, Roni (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Coral reefs are ecosystems in the sea formed by lime-producing marine biota, especially stony corals and calcareous algae, along with other biota that live on the ocean floor. Coral reefs are ecosystems that play an important role in coastal areas but are vulnerable to internal and external changes. The purpose of this study was to calculate the percentage of coral reef cover and assess the condition of coral reefs on the Kapoposang Island. Coral Point Count with Excel Extension (CPCE) was used to analyze coral reef data. The data used were photos of coral reefs taken using the Underwater Photo Transect (UPT) method from six observation stations scattered around Kapoposang Island. Each processed photo contained 30 randomly selected points. The results of the assessment of the condition of coral reef health at five stations showed that station 1 (one) 35.62% was in moderate condition, station 2 (two) 43% was in moderate condition, station 3 (three) 46.67% was in moderate condition, station 4 (four) 40.53% is in moderate condition, station 5 (five) 41.84% is in moderate condition and station 6 (six) 29.25% is in moderate condition. From the five data collection stations the condition of coral reefs on Kapoposang Island was in the moderate category with a percentage of 39.49%.